Response of Microphytobenthos and Benthic Bacteria Viability to Eutrophication in a Benthic–Pelagic Coupling Mesocosm Experiment - Tsikopoulou, Irini; Santi, Ioulia; Dimitriou, Panagiotis D.; Papageorgiou, Nafsika; Pitta, Paraskevi; Karakassis, Ioannis (Frontiers in Marine Science, 2020)
Excessive primary productivity due to nutrient inputs is a potential problem in coastal areas when resulting in high organic matter sedimentation rates. Microphytobenthos and heterotrophic bacteria are two components of the benthic ecosystem that contribute to nutrient cycling and decomposition of organic matter. In this context, the effects of nutrient addition and the associated in situ produced organic matter on microphytobenthos community composition and benthic bacterial viability were assessed in a mesocosm experiment for 58 days. The experimental setup included triplicate mesocosms filled with sediment and water under three levels of nutrient addition (‘control’, ‘low’ and ‘high’). Benthic algal community composition was assessed using chemotaxonomy and bacterial viability was estimated using flow cytometry and a double-staining protocol. Multivariate analysis detected a significant effect of treatment and time on microphytobenthic community composition indicating a difference between control and low mesocosms and also between low and high treatments at Day 12 and Day 24 of the experiment. Nonetheless, microphytobenthos implied high resistance and redundancy of benthic algae to disturbance as all three treatments showed no significant difference in community structure between Day 0 and Day 58. Bacterial viability responded quickly to the high nutrient addition and was significantly lower than in the ‘control’ and ‘low’ treatments at Days 6 and 12. Both pelagic and benthic environmental variables were correlated to these changes in benthic community.